The exploration of Indonesian students’ attributions in EFL reading and writing classes - Gai Mali, Yustinus Calvin (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2022)
Although the previous studies have given so much attention to exploring the students’ attributions in various settings and academic levels, there is a scarcity of research that presents and compares findings on the attributions of Indonesian university students, specifically in the reading (receptive skill) and writing (productive skill) courses. This study researched students’ attributions in their English as a Foreign Language (EFL) writing and reading classrooms at a private university in Indonesia. The research participants were 161 students who responded to an online questionnaire that explored their attributions for the success or failure in achieving the learning objectives of the classes. The study revealed that most of the students in both courses could successfully achieve the learning objectives, and there were no attribution differences in the courses. Their effort and positive teacher’s performances were mostly cited attributions for the success, whereas low ability and lack of effort were the primary attributions for some students’ failure in achieving the learning objectives of the classes. Practical strategies to support teaching and learning in the EFL reading and writing classes and directions for further research were presented.